FACTORS THAT INFLUENCE ENTREPRENEURIAL INTENTION USING THE THEORY OF PLANNED BEHAVIOR (A STUDY OF ENTREPRENEURS FROM TANAH GAYO) - Simanungkalit, Juli (Cattleya Darmaya Fortuna, 2025)
From the initial research that researchers did, nowadays, thenumber of entrepreneurs is still small and the quality is not yetgreat, so that the problem of Indonesian entrepreneurialdevelopment is an urgent issue for successful development. Thecause of this lack of interest has a negative view of society,including aggressive, competitive, selfish, dishonest, miserly,unstable, less respectable, low-income, and so on. The tendencyis that most students, including final year students, as well asscholars and masters who have just graduated do not have anentrepreneurial plan. The purpose of this study is to find out whatfactors influence entrepreneurial intentions using the theory ofplanned behavior.Entrepreneurs who come fromGayo Land). Thenumber of samples in this study amounted to 100 people usinginterview techniques. The analysis technique used is descriptiveanalysis method. The results of the study show that there aremany workloads, risks, challenges and changes that are beyondtheir initial expectations, and they must face it and have to find asolution. If they like their profession as entrepreneurs, they willlearn again and want to adapt again to the workload, risks,challenges and changes that will not affect them to quit theirprofession